The Effect Of Numbered Head Together (NHT) Cooperative Learning Model On Students Learning Outcomes On Human Respiratory System Materials At SMPN 2 Solok City - Sabrina, Nurul; Arif, Khairil (Universe, 2023)
The purpose of the study was to determine the effect of the NHT (Numbered Head Together) type cooperative learning model on student learning outcomes on the human respiratory system material at SMPN 2 Solok City. This research was conducted at SMPN 2 Solok City in the 2021/2022 academic year. The type of research used is Quasi Experiment. The research design that will be used is the Non-equivalent control group design. The sampling technique used is purposive sampling. The sample used is class VIII-7 as a control class using a conventional model while class VIII-8 as an experimental class using a cooperative learning model of the NHT type. The instrument used in this study was written in the form of multiple choice questions. While the test analysis was carried out using Microsoft Excel, the calculation of the hypothesis test was carried out with the t test after conducting the prerequisite test, namely the normality test and homogeneity test. The results of the t-test calculation are tcount = 3.96 and ttable = 1.67, where tcount> ttable, thus research H0 is rejected and H1 is accepted. This shows that there is an influence on the cooperative learning model type NHT (Numbered Head Together) on the cognitive learning outcomes of class VIII students on the human respiratory system material at SMP N 2 Solok City.